Impowerment of micro-enterprise though trademark protection - Pazos Hayashida, Javier (2017)
One of the most important devices to develop the small business is the correct use of the industrial property rights. As we know, the essential function of trademarks is to identify but they also work as a source and origin identifier and they are an assurance of quality function. However, the most important thing is that trademarks are a valuable device of publicity that allow to approach the small businessman to their products and services consumers.